PENGEMBANGAN MOBILE LEARNING BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN EKONOMI - M. Rifqi Lutfi Alhafidz; Agung Haryono (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
Learning media is a tool used by teachers in the process of learning activities that can help students to prepare and receive materials independently in learning anywhere and anytime. Along with the development of technology, one of the learning media that can be used for students that is smartphones. Many students use smartphones during the learning process just to access the internet, social networking and gaming so students prefer to use a smartphone for fun rather than study. This research aims to produce the application mobile learning based on android on the material of the role of economic agents in economic activities as an independent learning media in the students of class X IPS.This research is a development research that refers to Borg and Gall's modified development procedure into eight steps: (1) preliminary research and data collection, (2) planning, (3) product draft development, (4) expert validation, (5) ) revised product of expert valiation, (6) limited field trial, (7) revision of trial result, (8) final product. The data in this study were collected by questionnaire.Based on the result of the research, the feasibility test shows that the percentage of validity of the material expert validator is 86.15% which means it is very feasible to be used, from the expert expert media expert of 96% which means very feasible to be used, from the validator of economic learning practitioner (teacher) of 80, 91% which means worthy to be used, and students 78,28% which means feasible to use. So obtained the average percentage of eligibility of 85.33% which means that based android mobile learning applications are very feasible to use.Some development suggestions for further product perfection that is adding a more interesting appearance in the form of animation or video, adding other materials, and need to test the product so that can know the level of effectiveness of learning media products economy.